2018
DOI: 10.1177/1178646918802282
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, Nutrition, and Health Benefits of Tryptophan

Abstract: Tryptophan is an essential plant-derived amino acid that is needed for the in vivo biosynthesis of proteins. After consumption, it is metabolically transformed to bioactive metabolites, including serotonin, melatonin, kynurenine, and the vitamin niacin (nicotinamide). This brief integrated overview surveys and interprets our current knowledge of the reported multiple analytical methods for free and protein-bound tryptophan in pure proteins, protein-containing foods, and in human fluids and tissues, the nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(135 citation statements)
references
References 102 publications
(107 reference statements)
1
119
1
1
Order By: Relevance
“…Proteins and amino acids derived from dietary intake can positively influence sleep quality and duration by modulating neurotransmitters and neuromodulators expression [16]. Among the most studied, tryptophan, an essential amino acid, is of major interest because it acts as an upstream precursor of bioactive metabolites related to sleep, including serotonin and melatonin [17]. Glycine, a non-essential amino acid, may exert a positive action toward sleep quality by reducing the core body temperature exerting an excitatory and inhibitory role on neurotransmission via N-methyl-d-aspartate-type glutamate receptors and glycine receptors, respectively [18].…”
Section: Role Of Nutritional Components On the Brain: Micro-and Macromentioning
confidence: 99%
“…Proteins and amino acids derived from dietary intake can positively influence sleep quality and duration by modulating neurotransmitters and neuromodulators expression [16]. Among the most studied, tryptophan, an essential amino acid, is of major interest because it acts as an upstream precursor of bioactive metabolites related to sleep, including serotonin and melatonin [17]. Glycine, a non-essential amino acid, may exert a positive action toward sleep quality by reducing the core body temperature exerting an excitatory and inhibitory role on neurotransmission via N-methyl-d-aspartate-type glutamate receptors and glycine receptors, respectively [18].…”
Section: Role Of Nutritional Components On the Brain: Micro-and Macromentioning
confidence: 99%
“…Tryptophan (Trp) is large neutral amino acid (LNAA) and precursor for brain neurotransmitters (serotonin, melatonin, tryptamine, quinolinic acid and kynurenic acid). According to Friedman (2018), dietary Trp and its metabolites may contribute to the therapy of many diseases, cognitive function, depression, sleep and social function. However, this hypothesis is still under discussion (Soh and Walter 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mallek‐Ayadi, Bahloul, and Kechaou () found that Cucumis melo seed protein contains the 129.91 g tryptophan per kg protein. This melon seed protein containing the exceptionally high level of tryptophan might ameliorate the adverse effects of several diseases that have been reported for the amino acid tryptophan (Friedman, ). Clinical studies are needed to investigate this further.…”
Section: Resultsmentioning
confidence: 99%